The Absurdity of The Law In The Enforcement of Criminal Acts Fisheries (Illegal Fishing) in Indonesia - Muhammad Fauzi Ramadhan; Airlangga Putera; Miftahul Jannah (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
This research explores legal absurdities in Indonesian law enforcement for illegal fishing, focusing on the forms of absurdity and their impact. The author uses normative legal research to determine that the current legal absurdity in Indonesian law enforcement is due to the ratification of Law no. 11 of 2020 concerning Job Creation in the Maritime and Fisheries Sector, which disharmonizes norms with previous fisheries laws and regulations. This legal absurdity is evident in the unclear phrase